MRI evaluation of acute appendicitis in pregnancy. Issue 3 (19th February 2013) - Dewhurst, Catherine; Beddy, Peter; Pedrosa, Ivan
Abstract In recent years, magnetic resonance imaging (MRI) has become a valuable diagnostic tool for evaluation of acute abdominal pain in pregnancy. MRI offers an opportunity to identify the normal or inflamed appendix as well as a variety of other pathologic conditions that can masquerade clinically as acute appendicitis in pregnant women. Visualization of the normal appendix by MRI virtually excludes the diagnosis of acute appendicitis and may help reduce the negative laparotomy rate in this patient population. Here we discuss a comprehensive MRI protocol for evaluation of pregnant women with abdominal pain, focusing on the appearance and location of the normal and diseased appendix, and we describe an approach to diagnosing acute appendicitis and other conditions with MRI. J. Magn. Reson. Imaging 2013;37:566–575. © 2012 Wiley Periodicals, Inc.